A power generation system with integrated supercritical water gasification of coal and CO2 capture. (1st January 2018) - Chen, Zhewen; Zhang, Xiaosong; Han, Wei; Gao, Lin; Li, Sheng
Abstract: Supercritical water gasification (SCWG) is a promising clean coal technology. A new power generation system with integrated supercritical water gasification of coal andCO2 capture is proposed in this article. The gasification product consisted of H2, CO, CO2, CH4, and unreacted supercritical water is directly combusted with pure O2 to provide heat for other units of the system, and the combustion product is used for power generation in turbines. The combustion product consists only of CO2 and H2 O. Thus, the CO2 can be easily captured under atmospheric condition. The thermal efficiency of the system can reach 38.31%, while the CO2 capture rate is 100%. The energy and exergic balances are conducted. The exergy efficiency of the system is 38.56%. The system has advantages over most coal-fired power plants with oxy-combustion or post-combustion technologies and IGCC systems with pre-combustion technologies. Highlights: A power generation system with integrated coal gasification and CO2 capture is proposed. Energy and exergy balances are conducted for the system. A thermal efficiency of 38.31% is obtained when the CO2 capture efficiency is 100%. The system has advantages over coal-fired power plants with CO2 capture.